I try to prove this by proving $(a_n)$ is a Cauchy sequence. First, since $s_n = \sum|a_n - a_{n+1}| < \infty$, $s_n$ converges and thus $$\lim_{n\rightarrow \infty} |a_n - a_{n+1}| = 0$$ Then, for every $\epsilon > 0$, let $n_0 \in \mathbb{N}$ such that $\forall n \geq n_0, |a_n - a_{n+1}| < \frac{\epsilon}{n_0}$. Then I have $$|a_n - a_m| \leq |a_n - a_{n+1}| + \cdots+|a_m-1 + a_m| \\ < (m-n-1)\frac{\epsilon}{n_0}$$ Here I got stuck, what if $\frac{m-n-1}{n_0}>1$? How can I rewrite this equation so that it will be exactly less than $\epsilon$?Can anyone give me some suggestions?

  • 2
    $\begingroup$ $\lim_{n\rightarrow \infty} |a_n - a_{n+1}| = 0$ is not enough to imply convergence, so your approach cannot work. Consider $a_n = \log(n)$, so $|a_{n+1} -a_n| \to 0$ $\endgroup$
    – leonbloy
    Sep 9, 2015 at 2:39

1 Answer 1


Observe that $$a_n=a_1+\sum_{k=2}^n(a_k-a_{k-1}).$$ Since the series in question converges absolutely, it converges. So the right hand side has a limit and hence the left hand side must as well.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.